2016
DOI: 10.1155/2016/4013843
|View full text |Cite|
|
Sign up to set email alerts
|

Coronary Angiography Safety between Transradial and Transfemoral Access

Abstract: Background and Aim. The aim of study was to evaluate safety, feasibility, and procedural variables of transradial approach compared with transfemoral approach in a standard population of patients undergoing coronary catheterization as one of the major criticisms of the transradial approach is that it takes longer overall procedure and fluoroscopy time, thereby causing more radiation exposure. Method. Between January 2015 and December 2015, a total of 1,997 patients in LPS Institute of Cardiology, GSVM Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
6
15
0
Order By: Relevance
“…Some interventions may be technically challenging via the radial route due to the size of the technology required, e.g., large bore rotational atherectomy [8, 48]. Moreover, TRA is usually more demanding and needs longer procedural time in elderly patients because of the frequent presence of specific vascular abnormalities such as tortuosity, calcifications, or arterial loops [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some interventions may be technically challenging via the radial route due to the size of the technology required, e.g., large bore rotational atherectomy [8, 48]. Moreover, TRA is usually more demanding and needs longer procedural time in elderly patients because of the frequent presence of specific vascular abnormalities such as tortuosity, calcifications, or arterial loops [4].…”
Section: Discussionmentioning
confidence: 99%
“…The femoral approach had traditionally been the primary approach for most operators [1]. Following the first report of radial CAG by Campeau in 1989 and radial PCI by Kiemeneij et al in 1993, there is an increase in use of transradial access around the world [24]. The major advantage of the TRA is the reduction in the incidence of complications related to the site of puncture associated with early ambulation, reduction in hospital stay, and consequently reduction in costs, making way for interventions in an outpatient care regimen [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…The fluoroscopic time mean was 6.43 ± 3.42 min which also was close to our center transfemoral result; mean 5.9 ± 1.2. 15 These outcomes are somehow contrasting other published Trials 23 , 24 and matching others. 25 Also mean amount of contrast used in TRA in some published data was comparable to our.…”
Section: Discussionmentioning
confidence: 95%
“…Tewari et al also noted similar findings and observed the mean fluoroscopy time taken as 4.40 ± 3.55 min for TR and 3.30 ± 3.66 min for TF-CAG ( p < 0.001) while mean fluoroscopy time as 13.53 ± 2.53 min for TR and 12.61 ± 9.524 min for TF-PTCA ( p < 0.001) 42 . However, an Indian study conducted by Sinha et al found no significant difference in radiation dose as dose area product (24.2 ± 4.21 versus 22.3 ± 3.46 Gy cm 2 ; p = 0.43) and fluoroscopy time (2.46 ± 1.22 versus 2.83 ± 1.31 min; p = 0.32) between TRI and TFI, respectively 85 …”
Section: Consensus Recommendations From Access Radial™ Advisory Boardmentioning
confidence: 91%